Active Molybdenum‐Based Anode for Dehydrogenative Coupling Reactions. Issue 9 (5th February 2018) - Beil, Sebastian B.; Müller, Timo; Sillart, Sydney B.; Franzmann, Peter; Bomm, Alexander; Holtkamp, Michael; Karst, Uwe; Schade, Wolfgang; Waldvogel, Siegfried R.
Abstract: A new and powerful active anode system that can be operated in 1, 1, 1, 3, 3, 3‐hexafluoro‐2‐propanol (HFIP) has been discovered. In HFIP the molybdenum anode forms a compact, conductive, and electroactive layer of higher‐valent molybdenum species. This system can replace powerful but stoichiometrically required Mo V reagents for the dehydrogenative coupling of aryls. This electrolytic reaction is more sustainable and allows the conversion of a broad scope of activated arenes. Abstract : Electrochemically driven and with a reactivity comparable to that of Mo V reagents, a novel active anode system based on 1, 1, 1, 3, 3, 3‐hexafluoro‐2‐propanol and molybdenum mediates the dehydrogenative coupling of arenes.